PELATIHAN PENGEMBANGAN AKTIVITAS ICEBREAKING DALAM PEMBELAJARAN DI SMPN 229 JAKARTA - Agustina, Noni; Hardianti, Hardianti; Fajarwati, Diana (Jurnal Pengabdian Masyarakat AbdiMas, 2024)
Learning does not only involve the transfer of knowledge but also requires the active interaction and collaboration among students. One effective way to foster interaction and collaboration is by incorporating icebreaking activities in the classroom. An interview conducted revealed that teachers expressed a need for further development of icebreaking activities. As a response, a community service activity was initiated, involving the provision of training of teachers on the development of icebreaking activities in teaching and learning process. The training aimed to enhance teachers’ knowledge and professional skills to establish a fun learning atmosphere and motivate the students. The development of teachers’ knowledge and skill development can inspire them to design and implement effective icebreaking activities. This community service employed various methods, including lecturing, presentations, discussions, and simulations engaging 229 Junior high school, Jakarta. The finding suggested that the community service significantly contributed to improving the teachers’ knowledge and skills in developing icebreaking activities, fostering their students’ learning readiness, creating a conducive and enjoyable learning environment, and promoting social interaction among students and teachers. Furthermore, it has the potential to enhance students’ engagement in learning process, leading to improved academic performance.  Key words: icebreaking activities, social interaction, and collaboration